Intrapleural tissue plasminogen activator and deoxyribonuclease in complex pleural effusion and empyema, clinical outcomes, and predictors - Yub Raj Sedhai; Priyanka Bhat; Roshan Acharya; Nada Qaisar Qureshi; Fawaz Mohammed; Irfan Waheed; Tahir Muhammad Abdullah Khan; Muhammad Altaf Ahmed; Nisarfathima Kazimuddin; Akinchan Kafle; Rodney T. Steff; Karan Singh (Therapeutic Advances in Respiratory Disease)
Background: Complex pleural effusion and empyema (CPPE) is treated with intrapleural fibrinolytic therapy (IPFT) using tissue plasminogen activator (tPA) and deoxyribonuclease (DNase) We present our single-center retrospective observational data using a simplified regimen of coadministering six divided doses of tPA and DNase over the course of 3 days. Objective: To study the safety, utility, and clinical outcomes of IPFT. Design: This is a single-center retrospective study of patients who received co-administration tPA/DNase for CPPE over a period of 5 years. The primary outcome was successful treatment without the need for surgery. Secondary outcomes were bleeding risk, post-procedural pain, treatment complications, and all-cause mortality at 30 days and 6 months. We have tested the clinical role RAPID score (Renal function measured as urea, Age, fluid Purulence, Infection source, Dietary status measured as albumin) to predict treatment success, and all-cause mortality at 6 months. Results: A total of ( n  = 55) patients were included in the study. The mean age of the population studied was 67 (Interquartile range 57–74), including 47.3% male and 52.7% Female. 92.7% of the population studied was Caucasian. Comorbidities including chronic obstructive pulmonary disease, congestive heart failure, and Diabetes mellitus were present in 41.8%, 41.8%, and 43.6.% respectively. Patients were treated with tube thoracostomy with 14 French percutaneous pigtail catheters in 47 (85.5%) or 28–32 French chest tubes in 8 (14.5%) patients. Twenty-nine percent (16) of patients had acceptable clinical and radiographic improvement and did not require additional surgical or radiological intervention. Seventy-one percent (39) of patients required additional surgical drainage; video-assisted thoracoscopic surgery in 37, and open thoracotomy in 2 patients. The discriminating ability of the RAPID score for treatment success after IPFT was found to be poor (AUC: 0.601, 95% CI: 0.429–0.773, p  = 0.24). All-cause mortality at 6 months was 23.6% (13) of patients. The predictive ability of the RAPID score for mortality at 6 months was found to be poor (AUC: 0.640, 95% CI: 0.478–0.802, p  = 0.13). The optimal cutoff for the RAPID score for mortality was ⩾4, with 84.6% sensitivity and 46.3% specificity. Conclusion: Results of our single-center study suggest that IPFT can be safely adopted by small and mid-sized clinical centers, as the risk of bleeding is low. The results of coadministering tPA and DNase are safe, and it reduces the need for surgical intervention in nearly one-third of patients.